Vitamin c supplementation attenuates the increases in circulating cortisol, adrenaline and anti-inflammatory polypeptides following ultramarathon running - Peters, E. M.; Anderson, R.; Nieman, D. C.; Fickl, H.; Jogessar, V. (International Journal of Sports Medicine, 2001)
The effects of vitamin C supplementation on the alterations in the circulating concentrations of cortisol, adrenaline, interleukin-10 (IL-10) and interleukin-1 receptor antagonist (IL-1Ra) which accompany ultramarathon running were measured using immuno-chemiluminescence, radioimmunoassay and ELISA procedures. Forty-five participants in the 1999 Comrades 90 km marathon were divided into equal groups (n = 15) receiving 500 mg/day Vit C (VC-500), 1500 mg/day Vit C (VC-1500) or placebo (P) for 7 days before the race, on the day of the race, and for 2 days following completion. Runners recorded dietary intake before, during and after the race and provided 35 ml blood samples 15 - 18 hrs before the race, immediately post-race, 24 hrs post race and 48 hrs post-race. Twenty-nine runners (VC-1500, n = 12; VC-500, n = 10; P, n = 7) complied with all study requirements. All post-race concentrations were adjusted for plasma volume changes. Analyses of dietary intakes and blood glucose and anti-oxidant status on the day preceding the race and the day of the race did not reveal that carbohydrate intake or plasma vitamins E and A were significant confounders in the study. Mean pre-race concentrations of serum vitamin C in VC-500 and VC-1500 groups (128 +/- 31 and 153 +/- 34 &mgr;mol/l) were significantly higher than in the P group (83 +/- 39 &mgr;mol/l). Immediate post-race serum cortisol was significantly lower in the VC-1500 group (p < 0.05) than in P and VC-500 groups. When the data from VC-500 and P groups was combined (n = 17), immediate post-race plasma adrenaline, IL-10 and IL-1Ra concentrations were also significantly lower (p < 0.05) in the VC-1500 group. The study demonstrates an attenuation, albeit transient, of both the adrenal stress hormone and anti-inflammatory polypeptide response to prolonged exercise in runners who supplemented with 1500 mg vitamin C per day when compared to </= 500 mg per day.